Improvement of the Institutional and Economic Mechanism of the Region’s Natural Resource Potential Assessment - FROLOV, Sergey; SAMODAY, Valentyna; MASHYNA, Yuliya (Journal of Environmental Management and Tourism, 2016)
The peculiarities of the sustainable ecological development issue are strongly associated with the necessity to improve the use of the region’s natural resource potential, which is qualitatively and quantitatively characterized and territorially bound. Taking into account regional development decentralization and creation of the natural resources market, which foresees the owner’s status change, the expediency of the further optimization of institutional and economic mechanism of natural resource potential use on the basis of its complex assessment is considered. Consequently, there occurred a necessity to work out in detail economic essence of the notion of natural resource potential and to improve theoretical and scientific-methodological aspects of its assessment. Based on the structural characteristics of the natural resource potential as system, unique natural complex, which is characterized by close connections and hierarchic subordination of all its constituents, structurally logical notion of the region’s natural resource potential is formed. Scientific and methodological sources of natural resource potential, natural resources theory itself is the basis for formation of the region’s natural resource potential assessment, including fundamentally different approaches: comparative, cost and rent. Further, it is grounded, that rent approach is the most reasonable in the market economy, as differential rent withdrawal is not only an important source of the budget incomes of different levels and regulator of different kinds of activities in the territory context, but also a part of financial resources for preservation and reproduction of the region’s natural resource potential. In order to reveal the tendencies of the first kind differential rent value change under the influence of rent-generating factors change, functional dependence is offered. In the result of the research, theoretical and scientific-methodological approaches to the natural resource potential assessment were generalized and it is suggested to take into account dynamic nature of the rent-generating factors influence on the differential rent value as region’s natural resource potential assessment constituent.
Keywords: assessment of region’s natural resource potential; classification theories of natural resources; rentgenerating factors; differential rent